A Groswater Palaeoeskimo feature from Coachman's Cove, Newfoundland / Une structure paléoesquimaude groswatérienne à Coachman's Cove, Terre-Neuve - Erwin, John (Études/Inuit/Studies, 2003)
AbstractPalaeoeskimo dwellings on the Island of Newfoundland are comparable to Arctic and Sub-Arctic Palaeoeskimo structures insofar as they contain shared architectural features such as mid passages, stone pavements, box hearths, and sleeping platforms. On the Island, however, dwelling structures are often described as amorphous, poorly defined, and are often confused by multiple re-occupations. The present situation for Groswater Palaeoeskimo on the Island is perhaps even less well understood owing to the paucity of known sites with architectural remains. The description and analysis of Cow Cove 1 (EaBa-14) provides additional evidence for understanding Early Palaeoeskimo architecture, resource use and seasonality on the Island of Newfoundland.